OPTIMIZING CONVERSATIONAL COMPETENCE: UTILIZING COLLABORATIVE FRAMEWORKS TO ENHANCE SPONTANEOUS SPEECH PRODUCTION AMONG INTERMEDIATE-LEVEL LANGUAGE LEARNERS - Berdikulova Munira Azizovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Cultivating sustained verbal proficiency remains a complex hurdle within English language pedagogy, particularly for intermediate-level students transitioning from passive comprehension to active communication. Traditional approaches to oral instruction frequently depend on isolated presentations or scripted scripts that fail to mirror authentic human interaction. This paper analyzes the pedagogical value of structured peer collaboration and interactive group dynamics within higher education conversational courses. By establishing low-stress, interactive learning environments, these methodologies aim to reduce communicative apprehension and accelerate vocabulary retrieval. This study examines the structural design of interactive assignments, the evolving role of the instructor, and the measurable impact of collaborative tasks on student confidence. The outcomes indicate that when speaking exercises are carefully scaffolded through peer interaction, individual production time increases, collaborative correction thrives, and oral confidence is significantly elevated.